Tracing amino acid exchange during host-pathogen interaction by combined stable-isotope time-resolved Raman spectral imaging - Naemat, Abida; Elsheikha, Hany M.; Boiter, Radur; Notingher, Ioan (Nature Publishing Group, 2016)
This study investigates the temporal and spatial interchange of the aromatic amino acid phenylalanine (Phe) between human retinal pigment epithelial cell line (ARPE-19) and tachyzoites of the apicomplexan protozoan parasite Toxoplasma gondii (T. gondii). Stable isotope labelling by amino acids in cell culture (SILAC) is combined with Raman micro-spectroscopy to selectively monitor the incorporation of deuterium-labelled Phe into proteins in individual live tachyzoites. Our results show a very rapid uptake of L-Phe(D8) by the intracellular growing parasite. T. gondii tachyzoites are capable of extracting L-Phe(D8) from host cells as soon as it invades the cell. L-Phe(D8) from the host cell completely replaces the L-Phe within T. gondii tachyzoites 7–9 hours after infection. A quantitative model based on Raman spectra allowed an estimation of the exchange rate of Phe as 0.5–1.6 × 104 molecules/s. On the other hand, extracellular tachyzoites were not able to consume L-Phe(D8) after 24 hours of infection. These findings further our understanding of the amino acid trafficking between host cells and this strictly intracellular parasite. In particular, this study highlights new aspects of the metabolism of amino acid Phe operative during the interaction between T. gondii and its host cell.